2020
DOI: 10.3390/su12176925
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Energy Intensity Ratio for Carbon Dioxide Emissions in China

Abstract: Industrial carbon dioxide (CO2) emissions are mainly derived from fossil energy use, which is composed of procedures involving extraction of energy from the natural system as well as its exchange and consumption in the social system. However, recent research on low-carbon transitions considers the cost of energy commodities from a separate perspective—a biophysical or monetary perspective. We introduce the energy intensity ratio (EIR), which is a novelty perspective combining biophysical and monetary metrics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Liao et al [10] identified that the influencing factors of carbon emissions in electricity generation primarily encompass per capita GDP, electricity production structure, energy efficiency, coal consumption in power generation, technological advancements, population size, and industrial composition. Chen et al [11] introduced the energy intensity ratio, developed the EIR-LMDI method to explain the changes in CO2 emission from 2007 to 2018, and the results showed that changes in CO2 emissions caused by the EIR are the net energy effect.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [10] identified that the influencing factors of carbon emissions in electricity generation primarily encompass per capita GDP, electricity production structure, energy efficiency, coal consumption in power generation, technological advancements, population size, and industrial composition. Chen et al [11] introduced the energy intensity ratio, developed the EIR-LMDI method to explain the changes in CO2 emission from 2007 to 2018, and the results showed that changes in CO2 emissions caused by the EIR are the net energy effect.…”
Section: Introductionmentioning
confidence: 99%
“…In September 2020, at the 75th session of the United Nations General Assembly, China proposed that "it will increase the intensity of its nationally determined contributions, adopt more powerful policies and measures, strive to reach the peak of CO2 emissions before 2030, and strive to achieve carbon neutrality by 2060" [4][5][6] .To achieve the "double carbon" goal as soon as possible, China will accelerate the construction of a new power system to adapt to the gradual increase in the proportion of new energy [7][8]. As an essential ecological security barrier in the west of the country and the central hub of the Northwest power grid, Gansu Province plays a pivotal role in the country's environmental security [9][10][11]. The realization of the goal of carbon neutrality requires the joint efforts of various industries and departments in each province [12][13].…”
Section: Introductionmentioning
confidence: 99%